Effect of Social Marketing on Health Protocol Compliance Among Millennials in Jakarta, Indonesia - Simamora, Virgo; Rachma, Siti (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
Individual compliance with health protocols is a crucial factor in supporting Indonesian government in controlling the transmission of COVID-19, especially the millennial generation. This explanatory research aims to examine the effect of social marketing on compliance among millennials in Jakarta. Four indicators are applied to measure social marketing, and other two are applied to measure compliance. Using the questionnaire, the researcher collected data from 439 millennials. The hypothesis was tested using the partial least squares structural equation modeling (PLS-SEM). This study found that social marketing positively impacts compliance with health protocols. These findings have provided some empirical implications about how crucial social marketing increases millennials’ compliance with health protocols promoted to prevent and control COVID-19 transmission. The concept of the marketing mix, informing people about the benefits of health is critical since the social positive values offered by social marketers are a major incentive for people to follow health protocols.